2021
DOI: 10.3390/cancers13030374
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Neoplasms: Identification of Novel Metabolic Circuits of Potential Diagnostic Utility

Abstract: The incidence of neuroendocrine neoplasms (NEN) is increasing, but established biomarkers have poor diagnostic and prognostic accuracy. Here, we aim to define the systemic metabolic consequences of NEN and to establish the diagnostic utility of proton nuclear magnetic resonance spectroscopy (1H-NMR) for NEN in a prospective cohort of patients through a single-centre, prospective controlled observational study. Urine samples of 34 treatment-naïve NEN patients (median age: 59.3 years, range: 36–85): 18 had pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
4
0
1
Order By: Relevance
“…Trata-se de uma proteína que participa da composição do aparelho celular neuroendócrino. Sua sensibilidade gira em torno de 60% a 90% uma vez que um TNE já tenha sido identificado, todavia não é indicado o seu uso como ferramenta inicial, pois tem baixa precisão diagnóstica e prognóstica (Jiménez et al, 2021). O desenvolvimento de biomarcadores com adequados valores de sensibilidade e especificidade são imprescindíveis para que a investigação clínica seja mais acurada e que possibilite precocemente a terapêutica pertinente.…”
Section: Resultsunclassified
“…Trata-se de uma proteína que participa da composição do aparelho celular neuroendócrino. Sua sensibilidade gira em torno de 60% a 90% uma vez que um TNE já tenha sido identificado, todavia não é indicado o seu uso como ferramenta inicial, pois tem baixa precisão diagnóstica e prognóstica (Jiménez et al, 2021). O desenvolvimento de biomarcadores com adequados valores de sensibilidade e especificidade são imprescindíveis para que a investigação clínica seja mais acurada e que possibilite precocemente a terapêutica pertinente.…”
Section: Resultsunclassified
“…Several clinical studies have reported the stratified metabolic phenotype of various neuroendocrine neoplasmas to identify novel biomarkers for diagnosis and prognosis based on metabolic profiling of urine samples [ 35 ], tissue samples [ 36 ], and plasma samples [ 37 ]. It has been revealed that cell metabolism possessed heterogeneous characteristics and varied depending on the site and origin of tumors [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multianalyte analysis of neuroendocrine metabolites has also been explored as a diagnostic strategy for GEP-NENs. A 2021 study from Jiménez et al [ 85 ] used nuclear magnetic resonance to compare urine samples from patients with GEP-NENs and healthy controls and generated a model that could accurately discriminate between the two groups. The study suggests that nuclear magnetic resonance could be a useful clinical tool for diagnosing GEP-NENs[ 85 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…A 2021 study from Jiménez et al [ 85 ] used nuclear magnetic resonance to compare urine samples from patients with GEP-NENs and healthy controls and generated a model that could accurately discriminate between the two groups. The study suggests that nuclear magnetic resonance could be a useful clinical tool for diagnosing GEP-NENs[ 85 ]. They identified several metabolites that were either increased or decreased in GEP-NENs, including kynurenine, hippurate, and phenylacetylglutamine[ 85 ].…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation